Manual de prácticas sostenibles para el desarrollo del turismo rural en las comunidades del humedal la Segua del cantón Chone - Cedeño Mendoza, Gema Jomira (2019)
This research was developed with the purpose of structuring a manual of sustainable good practices that improves the tourism development of the La Segua wetland communities. For this, a three-phase methodology was established: the first consists of a situational diagnosis where it was evident that tourism products are scarce where communities are included, in addition to lacking tourist services such as accommodation, catering and basic services, making this unattractive sector. Several techniques and tools were used to execute this activity, such as review of official documents, interviews, EFI-EFE matrix, strategic SWOT. The second phase focused on identifying the impact of the productive activities of the communities, information that was compiled from official documents and on field visits in which it identified that the relevant lucrative activities are fishing, livestock, informal trade and tourist activity and its impact on the ecosystem, for which the Leopold matrix was used. The third phase focused on the structure of the manual of good sustainable practices where specific theoretical criteria are established for the existing problem and the relevant impacts of La Segua Wetland implementing sustainability programs are also described. Its structure consists of planning, design and operation focused on the activities of the population such as agriculture, livestock, fisheries and commerce, identifying the relevant impacts on the wetland and its surroundings creating sustainability programs and monitoring the application of said manual.